2020
DOI: 10.7759/cureus.7430
|View full text |Cite
|
Sign up to set email alerts
|

Giant Aneurysm of Coronary Artery Fistula Successfully Treated by Surgical Repair

Abstract: An asymptomatic 65-year-old woman was identified with an oversized round-shaped hypoechoic lesion (62 mm in diameter) between right and left atria by echocardiogram. A contrast-enhanced 320-slice multidetector computed tomography demonstrated a giant aneurysmatic fistula branched from the left main coronary trunk towards right atrium. The patient underwent an elective surgical repair. The aneurysm was resected, followed by coronary artery bypass graft surgery using bilateral internal thoracic arteries. The sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…In the diagnosis of CAFA, a comprehensive evaluation by combining diagnostic imaging modalities, including CAG and TTE, is important. The recent literature has reported that image information from contrast-enhanced 3D-CT is particularly useful [ 10 ]. In cases with renal dysfunction, cine-mode MRI, which does not use a contrast medium, might be useful for differential diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…In the diagnosis of CAFA, a comprehensive evaluation by combining diagnostic imaging modalities, including CAG and TTE, is important. The recent literature has reported that image information from contrast-enhanced 3D-CT is particularly useful [ 10 ]. In cases with renal dysfunction, cine-mode MRI, which does not use a contrast medium, might be useful for differential diagnosis.…”
Section: Discussionmentioning
confidence: 99%